Rekognisi Hukum Penggunaan Bahasa Asing dalam Pembuatan Akta Notaris Berdasarkan Ketentuan Hukum di Indonesia - Arif Budiman; Mohammad Ryan Bakry; Iskandar Muda (Syntax Idea)
In the Indonesian legal system, the use of foreign languages in making notarial deeds is a complex and significant issue. Notaries, as authorized public officials, are required to draw up deeds in Indonesian in accordance with Law on Notary Positions No. 2 of 2014 Article 43 and Law Number 24 of 2009 concerning the National Flag, Language and Emblem, as well as the National Anthem. This research aims to analyze the legal recognition of the use of foreign languages in notarial deeds and its implications for the validity of the deed. The research method used is normative juridical with a statutory approach and case studies. The research results show that although there are provisions requiring the use of Indonesian, there is still freedom in using foreign languages provided that the deed is translated by a sworn translator and included with the original deed. The conclusion of this research is that legal recognition of the use of foreign languages in notarial acts in Indonesia is strictly regulated to ensure clarity and validity of legal documents, as well as to protect the rights of the parties involved. The practical implication of these findings is the need for notaries to ensure compliance with language regulations to avoid potential legal disputes in the future